"The sociology of Stuart Hall". Issue 1 (2nd January 2018) - Hunter, Marcus Anthony
ABSTRACT: This brief essay animates two signature features of Stuart Hall's sociology, diaspora and culture, to draw attention to not only the paradigms manifest in his work but also how they point to fruitful paths to guide the future of the field. To do so, I will combine Hall's autobiographic account with key passages from his path-breaking essay 'What is this "Black" in Black Popular Culture?'. Here, then, the intention is to amplify Stuart Hall's place as a crucial innovator of sociological thought and research, while also drawing our attention to the path forward his work provides.